The Rise of Creative Hubs in Istanbul - Parlak, Meltem; Baycan, Tüzin (European Spatial Research and Policy, 2020)
This study investigates the emergence and the rise of Creative Hubs (CHs) in Istanbul, which as Turkey’s economic capital contains most of its creative workforce and the largest number of its CHs. In the last 10 years, the number of co-working spaces (CWSs), incubation centres (ICs), labs, and makerspaces in the city has rapidly increased, following a global trend. This study aims to better understand the changing working forms of the city by investigating the motivations behind the emergence of CHs. 46 CH examples, consisting of CWSs, ICs, makerspaces, and labs, have been examined for this purpose. The study is structured around the four main categories that highlight the different aspects of CHs: structure (establishment structure and community structure), focus (sectors and professions), services (physical and social facilities), and values (motivation). The findings of the study demonstrate that members of CHs are mostly freelancers, entrepreneurs, micro SMSs, and start-ups, consisting mostly of members of Generation Y. They work predominantly in creative sectors and tend to look for flexible and cost-saving solutions, support mechanisms, and new connections for their work. The research revealed that CHs are distinguished through the services that they provide. Having emerged as new forms to respond to the distinctive needs of emerging jobs in the creative economy era, they can be considered a new landscape of the post-industrial city.